THE EFFECT OF BALANCED NUTRITION EDUCATION WITH AUDIO VISUAL MEDIA ON STUDENTS KNOWLEDGE OF SDN 011 KAMBESKO - Anggreni, Elsie; Wulandhari, Yopi; Jas, Febby Pebrika (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2023)
Elementary school-age children are more at risk of experiencing nutritional problems related to diet and growth and development. Good nutritional status will affect the increase in knowledge in children through education, nutrition education is provided with the media so that it can attract the attention of elementary school children. Learning media using audio-visual was chosen because it has benefits for elementary school children in activating students' senses of sight and hearing so that they focus on the teaching and learning process. The purpose of this study was to determine the effect of providing audio-visual media on knowledge of balanced nutrition in elementary school children. The research design used was a Quasi-Experimental Pre-Test and Post-Test design. The research was conducted in Rengat City with a sample of 59 elementary school children. Paired Sample t-Test is used to see differences in knowledge before and after being given the audio-visual media. In this study it can be seen that there is a significant difference in knowledge of elementary school children (p <0.05), the results of the pre-test scores of students' balanced nutrition knowledge from before and after using audio-visual media, it can be seen that the pre-test value of knowledge of balanced nutrition is at range 3-7 with an average achievement (4.63%) while post-test scores are in the range 6-10 with an average achievement (8.69%). It can be concluded that the provision of audio-visual media can affect knowledge of balanced nutrition in elementary school childrenit is known that the sign.(2-tailed) value is 0.000 <0.005, then Ho is rejected and Ha is accepted, so it can be concluded that there is an average difference between the Pre Test of balanced nutrition knowledge of students before being given action with the average Post Test of balanced nutrition knowledge students after being given action, namely balanced nutrition education through the use of audio-visual media at SDN 011 Kambesko Rengat year 2023.